Cranberry‐lingonberry juice affects the gut and urinary microbiome in children ‐ a randomized controlled trial. Issue 3 (18th January 2023) - Hakkola, Mikael; Vehviläinen, Pekka; Muotka, Janita; Tejesvi, Mysore V.; Pokka, Tytti; Vähäsarja, Päivi; Hanni, Anna‐Maija; Renko, Marjo; Uhari, Matti; Salo, Jarmo; Tapiainen, Terhi
Abstract : The mechanism by which cranberry‐lingonberry juice (CLJ) prevents urinary tract infections (UTI) in children remains unknown. We hypothesized that it alters the composition of the gut or urinary microbiome. Altogether, 113 children with UTIs were randomly allocated to drink either CLJ or a placebo juice for 6 months. We collected urinary samples at 3 months and fecal samples at 3, 6 and 12 months and used next‐generation sequencing of the bacterial 16S gene. The children who consumed CLJ had a lower abundance of Proteobacteria (p = 0.03) and a higher abundance of Firmicutes phylum (p = 0.04) in their urinary microbiome at 3 months than did those in the placebo group. The abundance of Escherichia coli in the urinary microbiome was 6% in the CLJ group and 13% in the placebo group (p = 0.42). In the gut microbiome the abundance of Actinobacteria at 3 and 12 months was higher in the children receiving CLJ. The diversity of the urinary and gut microbiome did not differ between the groups. The children drinking CLJ had a different urinary and gut microbiome from those receiving a placebo juice. A healthy urinary microbiome may be important in preventing UTIs in children.